Truncated Estimation of Skating Force-Velocity Profiling When Using High-Speed Video-Based Methods Compared to Radar-Derived Processing - Perez, Jerome; Guilhem, Gaël; Brocherie, Franck (Frontiers in Bioengineering and Biotechnology, 2021)
This study aimed to compare the force-velocity biomechanical variables derived from high-speed video- and radar-based method during forward skating sprint in ice hockey. Thirteen elite female ice hockey players performed two 40-m forward skating sprints to determine, in the horizontal plane, maximal velocity reached, relative maximal theoretical force, maximal theoretical velocity, relative maximal power, linear slope of the force-velocity relationship, maximal value of the ratio of force and index of force application technique. Two different high-speed video-based methods adding a time shift (ST-TS) or not (ST) were used and independently compared to the radar-derived method. ST and ST-TS showed significant mean differences (all p < 0.002) compared to radar-derived processing for all variables except for maximal theoretical velocity (p = 0.26) and maximal velocity reached (p = 0.13) inferred from ST. In reference to radar-derived variables, ST-TS significantly induced larger lower values compared to radar of the main forward skating sprint determinants (force and power variables) and moderate-to-large overestimation for velocity variables. Correlations between ST or ST-TS and radar-derived methods ranged from trivial for velocity variables to very large for force and power variables. Consequently, practitioners must be aware that using such high-speed video-based methods would permit to determine biomechanical variables at the cost of much lower accuracy and reliability than the radar-derived method.